EFFECT OF DNFB IN COMBINATION WITH DIFFERENT CALCIUM ION CONCENTRATIONS ON VORTICELLA STALK CONTRACTION DYNAMICS - AMIT KUMAR VERMA,; ASHOK KUMAR SINGH, (The Bioscan, 2020)
DNFB (2,4-dinitrofluorobenzene) directly or indirectly affected biochemical performances of amino acid residues of the spasmins and batonnets, two different types of proteins found in Vorticella stalk and were responsible for both stalk’s contraction and coiling. DNFB exerted chemical stresses on protein conformations and thus produced pronounced effects on stalks’ contraction dynamics by means of differential data on frequency and duration of contraction-extension cyclic processes determined significant effects of DNFB concentrations from 1 mM to 5 mM threshold values on live specimens after incubation periods for more than 10 minutes in saline culture solutions and unable to affected rate of protoosmosis along the length of F-actins inside the spasmoneme of the stalk. But, it became able for tension generation on linkage-complexes and thus significantly established new force-pCa relations among protein cable connections above normal threshold values of protic potentials. Hence this study helped in understanding fundamental processes of stalk contraction at molecular level in the light of protoosmosis where energy expense was conserved by the system itself.